1999
DOI: 10.1006/redy.1998.0037
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Commodity Money, with Applications to Gresham's Law and the Debasement Puzzle

Abstract: What are the conditions under which Gresham's Law holds? And what are the mechanics of a debasement? To analyze these questions, we develop a model of commodity money with light and heavy coins, imperfect information, and prices determined via bilateral bargaining. There are equilibria with neither, both, or only one type of coin in circulation. When both circulate, coins may trade by weight or by tale. We discuss the extent to which Gresham's Law holds in the various cases. Following a debasement, depending o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
59
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 24 publications
3
59
2
Order By: Relevance
“…Weber continued the analysis of the Gresham's Law in [34], where the authors are proposing a model of commodity money and debasement. and prices determined via bilateral bargaining.…”
Section: Controversies On the Gresham's Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…Weber continued the analysis of the Gresham's Law in [34], where the authors are proposing a model of commodity money and debasement. and prices determined via bilateral bargaining.…”
Section: Controversies On the Gresham's Lawmentioning
confidence: 99%
“…After solving the model, the researchers found that there can be equilibrium with both coins in circulation. Since coins may trade "by weight" or "by tale", the extent to which Gresham's Law holds is discussed in [34] in the various cases.…”
Section: Controversies On the Gresham's Lawmentioning
confidence: 99%
“…E-mail address: yli@mx.nthu.edu.tw (Y. Li). 1 Some economists assert that a qualified version of Gresham's law requires a fixed exchange rate between the two monies (Friedman and Schwartz, 1963), but fixed exchange rate among various monies was not very often observed in history (see, for example, Rolnick and Weber, 1986;Velde et al, 1999). at the mint, and good money over-weight coins or money undervalued at the mint. Given what we know about history there had been times when bad money failed to drive out good, and many economists have questioned the empirical validity of Gresham's law.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to explain circulation of various monies and determine endogenously their exchange value, we need a model which leaves circulation and exchange value of money as an equilibrium result rather than an assumption. To account for this, Velde et al (1999) use a search-based model of commodity money without prior assumptions on exchange rates to study issues concerning the validity of Gresham's law and the mechanics of a debasement. They introduce private information by assuming that people are not always able to distinguish among various types of coins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation